A Comparison of Thermal Growing Season Indices for the Northern China during 1961–2015. (27th July 2017) - Cui, Linli; Shi, Jun; Ma, Yue
Abstract : Vegetation phenology is one of the most direct and sensitive indicators of terrestrial ecosystem in response to climate change. Based on daily mean air temperature at 877 meteorological stations over northern China from 1961 to 2015, the correlations and differences for different definitions of the growing season parameters (start, end, and length of the growing season) were investigated, and results show that higher correlations of 0.81–0.93 are found when indices which do not consider frost are compared with those of the same length which include the frost criteria, and lower correlations of 0.63–0.79 are observed when the length of indices is different and one of the indices includes the frost criteria or EI 3 (10 d < 5°C) is included. Lower correlations and larger differences are generally observed in the eastern and northwestern parts while higher correlation and smaller difference appeared in the northeastern and southwestern parts of northern China; thus the applicability comparison and selection of different definitions have important influence on the identifying and counting of the timing and length of the growing season in the eastern and northwestern regions of northern China.